LINGUOCULTUROLOGICAL CHARACTERISTICS OF IRONY - Parmonov Alisher Abdupattoyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Irony is essential part of linguistics, literature as well as stylistic. Moreover, linguoculturology is a new branch of linguistics. Also, learning irony in linguoculturological way is main subject of this article. Moreover, it show some differences between Uzbek and English irony